(untitled) (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2021)
The purpose of this activity is to provide insight and understanding about the importance of recording farming activities to the participants to be able to manage resources effectively and efficiently. The methods used in the training are extension, mentoring, discussion, and workshop methods. The results obtained during the training, overall activities including the materials and facilities provided received a very good response from all participants. Previously, participants were not familiar with fixed costs, depreciation and adjustment of fixed costs, variable costs, total costs, and R/C Ratio. However, after participating in the mentoring activities well, participants were able to apply farming activity analysis through 4 stages, namely recording, sorting, calculating, and deciding. So that the participants realized that recording farming activities was important to determine the condition of the farming business, namely in profit, breakeven or loss.